KUALITAS PAPAN PARTIKEL PALEM EKOR TUPAI (Wodyetia bifurcata) DAN KAYU AKASIA (Acacia mangium) BERDASARKAN KOMPOSISI BAHAN BAKU DAN KONSENTRASI PEREKAT - Sinaga, Kiki; Dirhamsyah, M; Yani, Ahmad (JURNAL HUTAN LESTARI, 2017)
The objective of this study is to investigate the influence of raw material from foxtail palm and acacia wood, and adhesive concentrate of urea formaldehyde composition for producing high quality of particle board. To compare the result quality standard of JIS A5908-2003 is utilized. The stages of research started by selecting the particle size, particle board mixing and formation to the test. The components that form the particle board are acacia wood, foxtail palm and urea formaldehyde. It is expected the amalgam of both wood particles have density of 0,7 gr/cm³. Specimens were made with the composition variation of 100% foxtail palm, 70% foxtail palm : 30% acacia wood, 50% foxtail palm : 50% acacia wood and with adhesive concentrations of 10%, 12% and 14%, those amalgams are then heated in 140ºC by pressure of 25 kg/cm³ for 10 minutes. The particle board is tested physically and mechanically. Of the variations in composition and adhesive concentration, the composition of 70% foxtail palm: 30% acacia wood with a concentration of 14% was good to be used in the manufacture of foxtail palm particle board. The foxtail palm particle board: acacia wood has an optimum modulus of elasticity value of 12661,7347 kg/cm² and the optimum modulus of rapture of 183,4028 kg/cm². In general, foxtail palm particle board: acacia wood meets the JIS A 5908-2003 standards except the value of the MOE. Keywords: Adhesive concentratio, Foxtail palm and Acacia wood, Particle board, Raw material composition